TEKNOLOGI SETNET DAN ATRAKTOR CUMI-CUMI: SUATU ULASAN PERKEMBANGAN DI INDONESIA - Mulyono S. Baskoro; Roza Yusfiandayani; P. Ika Wahyuningrum (Buletin PSP, 2008)
Indonesia has coastal and ocean natural resources which is potential to develop economic and welfare of the nation. Natural resources utilization has to maintain carrying capacity. Development of technology is needed to improve social welfare as well as maintain sustainability of the resource for sustainable utilization. Set net and squid attractor are such a way to develop integrated coastal area in order to empower coastal society. Set net is a fishing gear include in traps. This fishing gear can be developed because it has some advantages compare to another, such as can be integrated with sea farming and sea recreational, also efficient in energy uses. Squid attractor can be developed with aim to enrich squid stock in a certain water as well as to develop alternative livelihood for coastal society.